2020
DOI: 10.1186/s12889-020-09809-9
|View full text |Cite
|
Sign up to set email alerts
|

Addressing sickness absence among adolescents and young adults: an evaluation of the Medical Advice for Sick-reported Students intervention

Abstract: Background Sickness absence is associated with lower school achievements and early school leaving. The Medical Advice for Sick-reported Students (MASS) intervention is a proactive school-based intervention focused primarily on early identification and reduction of sickness absence. This study used a program evaluation framework to evaluate the MASS intervention among intermediate vocational education students and Youth Health Care professionals. Outcome indicators were primarily number of sick … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…In order to prevent young people from dropping out of school, the intervention ‘Medical Advice for Sick-reported Students’, abbreviated as MASS, is offered to all children in vocational and secondary education. MASS aims to optimise students’ health and maximise students’ participation in school activities and has been shown to be effective in reducing sickness absence rates in secondary schools [ 29 ] and vocational education [ 30 ]. MASS is currently being developed and evaluated for primary education [ 31 ].…”
Section: Preventive Child and Youth Healthcarementioning
confidence: 99%
“…In order to prevent young people from dropping out of school, the intervention ‘Medical Advice for Sick-reported Students’, abbreviated as MASS, is offered to all children in vocational and secondary education. MASS aims to optimise students’ health and maximise students’ participation in school activities and has been shown to be effective in reducing sickness absence rates in secondary schools [ 29 ] and vocational education [ 30 ]. MASS is currently being developed and evaluated for primary education [ 31 ].…”
Section: Preventive Child and Youth Healthcarementioning
confidence: 99%
“…Research in secondary education has shown that sickness absence can have many different causes, not just physical illness, but also social, psychological and lifestyle problems (Vanneste et al, 2015 ). Whatever the cause, finding the right care through cooperation between school, parents, students and youth healthcare physicians helps to solve underlying problems and reduce absenteeism (van den Toren et al, 2020 ; Vanneste et al, 2016 ). Research in primary education suggests that some children, with additional education needs or challenges at home, are absent more often, which can increase their educational and social disadvantages (Pijl et al, 2021 ; Roelofs et al, 2021 ; Vanneste, 2015 ).…”
Section: Introductionmentioning
confidence: 99%